PROFESSIONAL JUDGEMENT OF AN ACCOUNTANT WHILE CHOOSING THE CRITERIA OF MATERIALITY - VALENTINA Sitnikova (Учёт. Анализ. Аудит, 2019)
The development of the accounting system is accompanied by an increase in the number of situations, when the facts of economic activities are reflected depending on judgments, especially on the criteria of materiality.The article considers two groups of materiality criteria, which are the result of the professional judgment of an accountant and are therefore necessary for the reflection of the facts of economic activity in the accounting system as well as the disclosure of the information about the financial condition and the financial results of the organization in accounting (financial) statements.Approximate approaches to the identification of criteria in various situations basing on the requirements of normative documents are proposed in the article.The necessity of applying analytical indicators as the criteria for the identification of significant changes in the financial position of the organization is justified, which creates an impact on the disclosure procedures in the accounting (financial) statements.Thorough and elaborate development of the combination of the materiality criteria in the accounting system will help to ensure the increased quality level of accounting information.